Data Visualization on Mobile Devices - Lee, Bongshin; Brehmer, Matthew; Isenberg, Petra; Langer, Ricardo; Dachselt, Raimund (Extended Abstract of the 2018 ACM Conference on Human Factors in Computing Systems (CHI), 2018)
WORKSHOP ABSTRACT: As mobile visualization is increasingly used and new mobile device form factors and hardware capabilities continuously emerge, it is timely to reflect on what has been discovered to date and to look into the future. This workshop will bring together researchers, designers, and practitioners from relevant application and research fields, including visualization, personal informatics, and data journalism. We will work on identifying a research agenda for mobile data visualization as well as to collect and propagate practical guidance for mobile visualization design. Our overarching goal is to bring us closer to making an effective use of ubiquitous mobile devices as data visualization platforms.